Growth of Pennisetum purpureum cv. Taiwan with different sources of fertilization in bovine grazing - Guerra-Medina, Cándido Enrique; Ley-de Coss, Alejandro; Reyes-Gutiérrez , José Andrés; Aveldaño-Arrazate, Carlos Hugo; Vicente-Pérez, Ricardo; Montañez-Valdez, Oziel Dante (Ecosistemas y Recursos Agropecuarios, 2021)
The objective of the study was to evaluate the effect of two sources of fertilization on the nutritional value, growth characteristics and persistence of Taiwan grass in intensive grazing conditions of growing calves. The study was carried out in the municipality of Tapachula, Chiapas, Mexico. Two sources of fertilization applied to Taiwan grass after calf grazing were evaluated; three treatments in a randomized block design; 1) without fertilization, 2) humic fertilizer, 3) granular fertilizer. Two uniform cut heights after grazing; 1) without uniformity cut; 2) cutting height at 30 cm, 3) cutting height at 50 cm. An analysis of variance and means tests were applied to all the variables, to observe the differences between treatments. The crude protein content increased from 7.99% to 9.31% and 11.87% in the treatments: Taiwan grass without fertilization (TS); Taiwan + humic fertilizer (TH); Taiwan + granular fertilizer (TG) respectively; there was no effect of the applied treatment in most of the variables (P> 0.05); while leaf length was less (P